The Negative Effect of Work Environment and Team & Co-Worker Toward Employee Burnout: Testing The Mediating Role of Engagement - Angela, Clara; Yustina, Andi Ina (Indonesian Journal of Social Research (IJSR), 2023)
Due to its relevance to businesses, employee engagement has been the subject of extensive study, and many scholars have linked it to burnout as its antipode. The work environment and team and co-worker interactions promote engagement and reduce burnout if well-managed. This study investigates the function of engagement as a mediator between the indirect effects of work environment, team, and co-worker relationships on employee burnout. Respondents are sourced from a public firm employee (Tbk). Using SEM-PLS, three hundred thirty-one obtained data are processed. The results indicate that burnout is negatively related to the work environment and team and co-worker relationships and that employee engagement somewhat mediates these relationships. To mitigate burnout, an additional study can investigate employee satisfaction and performance.